The Effects of Mental Languishing on the Work Life of Healthcare Workers - Aydın, Delal; Demır, Ozcan (My University, 2025)
This study aims to explore the phenomenon of languishing among healthcare workers and its impact on their quality of work life, job performance, and coping strategies. Due to the lack of a specific languishing scale, the Mental Health Continuum-Short Form (MHC-SF) and General Health Questionnaire (GHQ-12) were utilized, with 200 healthcare professionals (doctors and nurses) participating in the study. The findings revealed that 47% of the participants exhibited signs of languishing, and this condition was negatively correlated with job satisfaction. Additionally, the results indicated that the languishing experienced by healthcare workers adversely affected their quality of work life and led to a decline in their overall performance.
Keywords: Work Motivation; Languishing; Mental Stagnation